Peningkatan Hasil Belajar IPA Siswa Kelas V Materi Perpindahan Kalor Melalui Model Cooperative Learning Type STAD di SDN Cinere 1 Depok - Hermawan, Cecep Maman; Rosfiani, Okta; Agil, Pujoseno; Zaky, Fauzan; Putri, Alviana (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2024)
Based on the learning results of class V students in Negeri Cinere 1 Depok, this research concluded that the science learning outcomes about heat transfer were mostly below the 75 KKM threshold. Only six out of 34 female students were able to reach the KKM. Therefore, it is necessary to improve science lessons on Heat and its Transfer using the STAD cooperative learning method. The aim of this research is to improve student learning and achieve the expected results. To improve student learning outcomes in understanding behavior changes, the STAD cooperative learning method is provided. For this reason, this research method uses a system consisting of observation, execution, discussion and reflection. Research findings show that using this method leads to increased student learning comprehension each semester. In practice, only 6 of 34 students (17.6%) met the requirements for the course in KKM 75. In the first sample, there were 18 people (52.94%). In contrast, the number of people in cycle 2 increased to 31 (91.18%). The results of this research can improve learning outcomes. The findings of this research indicate that the STAD collaborative learning method can improve student learning outcomes in class V at SDN Cinere 1 in Depok when it comes to the topic of science material and its transfer.